2008
DOI: 10.1200/jco.2008.16.1893
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal Obstructive Syndrome Diagnosed With Superparamagnetic Iron Oxide–Enhanced Magnetic Resonance Imaging in Patients With Chemotherapy-Treated Colorectal Liver Metastases

Abstract: SOS is present in a significant proportion of patients with treated colorectal metastases and is effectively detected on SPIO-enhanced T2-weighted GRE images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 55 publications
5
80
1
1
Order By: Relevance
“…This finding has recently been confirmed by Ward and coworkers [28], who showed that ferucarbotran-enhanced MRI had an 83% PPV for the detection of moderate to severe sinusoidal dilatation, largely associated with oxaliplatin-based chemotherapy. They suggest that locally impaired Kupffer cell function is responsible for the patchy iron uptake observed.…”
Section: Discussionsupporting
confidence: 56%
“…This finding has recently been confirmed by Ward and coworkers [28], who showed that ferucarbotran-enhanced MRI had an 83% PPV for the detection of moderate to severe sinusoidal dilatation, largely associated with oxaliplatin-based chemotherapy. They suggest that locally impaired Kupffer cell function is responsible for the patchy iron uptake observed.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have demonstrated that CT and/or MRI scans may provide excellent strategies for the screening of oxaliplatin-induced HSOS (8,10,11,16). In the present study, heterogeneous and predominantly hypoattenuation of the hepatic parenchyma was a distinctive radiological sign of oxaliplatin-induced HSOS on the CT scan.…”
Section: Discussionmentioning
confidence: 48%
“…Oxaliplatin-based regimens have been associated with the development of injury to the hepatic parenchyma in the form of hepatic sinusoidal obstruction syndrome (HSOS) (3)(4)(5)(6). Since oxaliplatin-induced severe hepatic sinusoidal obstruction was first reported in 2004 (7), oxaliplatin-induced hepatic injury has become a major concern in patients with metastatic colorectal cancer (8)(9)(10)(11). To the best of our knowledge, there have been no previously published reports on oxaliplatin-induced HSOS in other types of solid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This means that SPIO enhanced MRI, in this study, had a sensitivity of 87%, specificity of 89%, PPV of 83% and NPV of 92% for the presence of SOS. [69] In contrast to these findings however O'Rourke et al in their study of 37 patients found that SPIO enhanced MRI had a high specificity (100%) and PPV (100%) for the presence of severe SOS but a low sensitivity (11%) with a NPV of 78% suggesting that this technique may fail to identify a significant proportion of patients with SOS. [67] Grade Description Table 2.…”
Section: Radiological Assessment Of Chemotherapy Induced Liver Injurymentioning
confidence: 84%
“…[67] Grade Description Table 2. Grading of reticular hyperintensity on SPIO enhanced MRI to determine the presence of SOS [69] Shin et al explored the ability of Gadoxetic acid disodium (EOB-MRI; Primavist®) enhanced MRI to detect the presence of SOS prior to resection of colorectal metastases. On EOB-MRI the presence of SOS appears as reticular hypointensity which the authors graded on a scale of 1-5 with a score of 4 (probably present) or 5 (definitely present) being considered diagnostic of SOS.…”
Section: Radiological Assessment Of Chemotherapy Induced Liver Injurymentioning
confidence: 99%